Oral Administration of Probiotics Increases Paneth Cells and Intestinal Antimicrobial Activity - Cazorla, Silvia I.; Maldonado-Galdeano, Carolina; Weill, Ricardo; De Paula, Juan; Perdigón, Gabriela D. V. (Frontiers in Microbiology, 2018)
The huge amount of intestinal bacteria represents a continuing threat to the intestinal barrier. To meet this challenge, gut epithelial cells produce antimicrobial peptides (AMP) that act at the forefront of innate immunity. We explore whether this antimicrobial activity and Paneth cells, the main intestinal cell responsible of AMP production, are influenced by probiotics administration, to avoid the imbalance of intestinal microbiota and preserve intestinal barrier. Administration of Lactobacillus casei CRL 431 (Lc 431) and Lactobacillus paracasei CNCM I-1518 (Lp 1518) to 42 day old mice, increases the number of Paneth cells on small intestine, and the antimicrobial activity against the pathogens Staphylococcus aureus and Salmonella Typhimurium in the intestinal fluids. Specifically, strong damage of the bacterial cell with leakage of cytoplasmic content, and cellular fragmentation were observed in S. Typhimurium and S. aureus. Even more important, probiotics increase the antimicrobial activity of the intestinal fluids at the different ages, from weaning (21 days old) to old age (180 days old). Intestinal antimicrobial activity stimulated by oral probiotics, do not influence significantly the composition of total anaerobic bacteria, lactobacilli and enterobacteria in the large intestine, at any age analyzed. This result, together with the antimicrobial activity observed against the same probiotic bacteria; endorse the regular consumption of probiotics without adverse effect on the intestinal homeostasis in healthy individuals. We demonstrate that oral probiotics increase intestinal antimicrobial activity and Paneth cells in order to strengthen epithelial barrier against pathogens. This effect would be another important mechanism by which probiotics protect the host mainly against infectious diseases.